1982
DOI: 10.1007/bf01850989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged cold injury on the subcutaneous microcirculation of the hamster

Abstract: An animal model is described allowing for direct measurements of local tissue PO2, microhemodynamics and vascular density in the event of a prolonged non freezing cold injury. The model consists of implanting a transparent skin fold chamber in the dorsal skin fold in hamsters and of inserting two permanent indwelling catheters in jugular vein and carotid artery, respectively. The microcirculation was studied using a Wild Photomacroscope for photography and a platinum multiwire electrode for measurements of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Eventually, these results and further studies may provide more insight into the association between peripheral/core body temperatures and the induction of hibernation, with possible consequences for the understanding of injuries due to hypothermia [5], low temperature organ preservation techniques and induced or re-routed blood circulation [2,10]. a) Data are represented as the mean ± SD of body temperature for the period of days taken to reach the dropping point after logger implantation as shown in Table 2.…”
mentioning
confidence: 99%
“…Eventually, these results and further studies may provide more insight into the association between peripheral/core body temperatures and the induction of hibernation, with possible consequences for the understanding of injuries due to hypothermia [5], low temperature organ preservation techniques and induced or re-routed blood circulation [2,10]. a) Data are represented as the mean ± SD of body temperature for the period of days taken to reach the dropping point after logger implantation as shown in Table 2.…”
mentioning
confidence: 99%
“…17 Studies measuring tissue oxygen tension in nonfreezing cold injury models have demonstrated hypoxia and local tissue anoxia, both subcutaneously and intramuscularly, during cooling. 7,23 Cold injury is also known to reduce blood flow, induce vasopressor changes, 8 increase the viscosity of the blood, 24 and cause platelet aggregation. 10,33 It has also been pointed out that, although hypothermia reduces the rate of cellular metabolism, the poor perfusion of capillaries results in insufficient oxygen being released to meet the needs of surrounding tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Pronounced inflammatory reactions after infliction of a non-freezing cold injury provoke transient or permanent tissue damage [12]. Such effects on tissue integrity are explained on the basis of rheological changes, which include variations of local hematocrit and a tendency of red blood cells to aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…While the experimental evidence of a significant microhemodynamic impact seems poor at present for the first of these two factors, the enhanced capability of white blood cells and platelets to adhere to the vascular endothelium may lead to an elevation of local flow resistance and thereby enhance perfusion heterogeneity [15]. The latter phenomenon could be of particular significance during a chronic exposure to low temperatures, because the microvasculature would be plugged by blood cells, resulting in tissue hypoxia [12,23]. The mechanism of such microvascular occlusion, however, remains obscure, because an analysis of capillary ultrastructure during chronic, repeated cold exposure is not available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation